Spiders in Brazil: from arachnidism to potential therapeutic use of their venom part 2 of 2 - de Moraes Scopel Borges, Julia; Carvalho de Andrade, Ana Karolina; Alves Ferrareis, Lis; Ferreira Trindade, João Victor; Salvador Pereira Montenegro, Stefânia; Soares de Souza Lima Rodrigues, Bruna; Balbino Miguel, Paulo Sérgio; Siqueira-Batista, Rodrigo (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
Arachnidism, spider envenomation, is an important public health issue in different parts of the world. Its clinical evolution depends on the genus involved. Symptoms and signs range from skin alterations to systemic manifestations. The success of treatment, consisting of serotherapy and other measures, depends on the patient’s immediate care. In addition to the potential injury to human hosts, spider venom has been investigated for the therapy of various diseases. Based on these considerations, this article, part 2 of 2, aims to present the main aspects of spider accidents, focusing on clinical findings, diagnosis, differential diagnosis and treatment, as well as highlighting the potential of the venom of these arachnids. KEY WORDS: spiders; spider bites; spider venom.